Detection of Vulnerable Plaques in Middle-Aged and Elderly Patients With Coronary Heart Disease Complicated With Diabetes Mellitus By Combined Use of Coronary CTA, UA and APOB/A I ratio - Jin, Jingjing; Qi, Chunmei; Peng, Cheng; Hao, Ji; Cai, Wenbiao; Zhang, Qingdui; Wu, Jingyu; Sun, Huamei; Guo., Ziwei (Cardiology and Cardiovascular Medicine, 2019)
Objective: To explore the clinical value of 256-slice spiral CT coronary angiography combined with serum uric acid (UA) and apolipoprotein B/A I (ApoB/A I) ratio in detecting vulnerable coronary plaques (VP) in middle-aged and elderly diabetic patients. Methods: 1. Patients hospitalized in the Department of Cardiology, Second Affiliated Hospital of Xuzhou Medical University from January 2016 to January 2018 with diabetes mellitus and coronary CTA diagnosed as coronary heart disease were divided into three groups according to the nature of plaque: 28 vulnerable plaque group, 30 mixed plaque group and 25 calcified plaque group. 26 patients with simple DM and without coronary plaque group were included as control group and other patients in DM group. Three groups were compared.2. Record the general data of the subjects. All the subjects were treated with UA, ApoA I, ApoB, FIB, FPG and TG after admission. Results: There were significant differences in UA and ApoB/AI ratios among groups (P < 0.05). Logistic regression analysis showed that FIB, ApoB, UA and ApoB/AI were independent risk factors for vulnerable plaques (P < 0.05). Conclusion: The ratio of UA to A poB/A I is an independent risk factor for vulnerable plaque in middle-aged and elderly patients with coronary heart disease and DM. The ratio of coronary CTA combined with UA and A poB/A I has important clinical value in predicting the vulnerability of plaque in middle-aged and elderly patients with coronary heart disease and DM.